The Character-Building Reconstruction Based on Local Wisdom (Adoption of Empathy Values in Sèsèt Jâmbul Song) - Moh. Wardi; Syaifatul Jannah; Luthfatul Qibtiyah; Wardatus Syarifah; Khodijah (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
This article examines the values ​​of empathy in the sèsèt jambul song as an effort to shape the character of students based on local wisdom. Observing the many cases of violence between children, it is undeniable that one of them is caused by a lack of empathy so that it is necessary to review the teaching and learning process that takes place in schools. In this case, the empathetic value contained in the Sèsèt Jambul song can be adopted by the teacher as an effort to build character. The research method uses a descriptive qualitative approach. Data collection techniques used are documents and in-depth interviews. The data source for this research is the book Collection of Madurese Songs composed by Adrian Pawitra. The process of data analysis used the Gadamerian hermeneutic analysis technique, namely the method of analyzing the interpretation of meaning in the text. The results showed that there were three values ​​of empathy in the sèsèt jambul song which could be adopted as an effort to shape the character of students, namely not being selfish, caring, and alert to help. Unselfish attitude of students who do not win alone. Caring is an attitude of compassion towards others. Alert to help is a light-hearted attitude to help others.